Analisis Perbandingan Degree ff Financial Leverage Antara Pt. Japfa Comfeed Indonesia Tbk dan Pt. Charoend Pokphand Indonesia Tbk - Saodah, Saodah; Alwi, Alwi (PT. Alahyan Publisher Sukabumi, 2023)
This study aims to analyze whether or not there is a difference in the Degree of Financial Leverage between PT. Japfa Comfeed Indonesia Tbk and PT. Charoend Pokphand Indonesia Tbk. The type of research used in this research is comparative research (comparison). Comparative research is used to determine the comparison of the Degree of Financial Leverage between PT. Japfa Comfeed Indonesia Tbk (X1) and PT. Charoend Pokphand Indonesia Tbk (X2). The variable in this study is DFL (Degree of Financial Leverage). The sampling method used was a purposive sampling method, namely taking a sample that was determined previously based on the aims and objectives of the research and the sample in this study was the financial statements at PT. Charoend Pokphand Indonesia Tbk and PT. Charoend Pokphand Indonesia Tbk for 10 years starting from 2012 to 2021. The data analysis used was in the form of a t-test of two independent samples. The results of the analysis show that there is a significant difference in the Degree of Financial Leverage between PT. Japfa Comfeed Indonesia Tbk and PT. Charoend Pokphand Indonesia Tbk, the results of data interpretation can be compared tcount and ttable. If tcount ≥ table, then H0 is accepted and Ha is rejected. So (2.534) ≥ (2.306), then H0 is rejected and Ha is accepted.